DEVELOPMENT OF INTEGRATED EDUCATIONAL PROGRAMS IN THE FIELD OF PHYSICAL CULTURE AND SPORTS FOR PUPILS OF BOARDING SPORTS SCHOOLS AND SPECIALIZED SPORTS CLASSES - Harry Z. Karnaukhov; Irina I. Grigorieva; Dmitri N. Chernonog (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Modern Russian and foreign experience of training elite athletes and sports reserve national team shows the need for integration of the work of educational institutions and organizations engaged in athletic training. Getting exclusive education can be achieved through the development of a system of boarding schools of athletic profile. The article presents the principles of operation of boarding schools of sports profile, and also features the development of integrated programs and curricula for training of sports reserve without interrupting the educational process. Boarding schools of sports profile implement integrated programs that can adjust the performance of the educational process, to include the goals and objectives of other subject areas and to increase the volume of subject disciplines, such as "scientific subjects" and "Philology".